Sabun Cair Cuci Tangan Berbasis Ekoenzim Inovatif dari Limbah Buah dan Sayur Menggunakan Gula Pasir dan Gula Aren: Solusi Antibakteri Berkelanjutan Melawan Bakteri Gram-Positif dan Gram-Negatif Pendukung SDGs dan Inisiatif Kesehatan Nasional - Umarudin Umarudin; Ninik Mas Ulfa; Silvi Ayu Wulansari; Ramadhan Renaisansa; Selvyronica Eka Agustine; Aisyah Hadi Ramadani (Jurnal Penelitian Pendidikan IPA, 2026)
Indonesia's abundant fruit/vegetable waste threatens the environment yet fuels sustainable hygiene innovation. The waste will be fermented anaerobically with sugar and palm sugar. The study will also assess the soap's efficacy against Staphylococcus aureus (Gram-positive) and Escherichia coli (Gram-negative). To achieve this, we produced an eco-enzyme by anaerobic fermentation. We then incorporated 5–10% of this enzyme directly into a pre-heated soap base. A hybrid hot-cold process was used: first, hot mixing ensured homogeneity; next, cold stabilisation was applied. pH testing and agar well diffusion assays followed. Results: Dose-response assays yielded significant (p < 0.05) increases in inhibition zone size; palm sugar at 10% excelled (35.3 mm E. coli, 23.6 mm S. aureus), surpassing commercial products. ANOVA followed by Tukey's post hoc (α = 0.05) showed that sugar variants (23.9 mm E. coli, 22.3 mm S. aureus) outperformed controls. pH: F0 8.83, F1 5.26, F3 4.79. Discussion: Remarkably, the exceptionally broad 35.3 mm E. coli zone reveals a groundbreaking novelty: unprecedented Gram-negative hyper susceptibility contrary to LPS resistance norms uniquely triggered by eco-enzyme organic acids synergising with palm sugar gallotannins to breach outer membranes. These zero-waste breakthroughs advance SDGs 3 and 12 by pioneering bio-circular antimicrobials.